Islamic Appraisal of Women’s Participation in Handwork Business for Economic Development in Doma LGA, Nasarawa State. - Salamatu Ibraheem Atukpa; Ishaka Bala Ishaka; Bako Sa'ad Adamu (Equality: Law and Social, 2025)
This study examines the Islamic perspective on women’s participation in handwork business as a means of promoting economic development in Doma, Nasarawa state. Using mixed-method approach, the study investigates the Islamic principles and values that influence women’s involvement in handwork business, and explores the economic benefits of women’s participation in this sector. The study findings have implications for policy makers, entrepreneurs and Islamic leaders seeking to promote economic development and women’s empowerment in Doma, Nasarawa state. The findings of this study reveal that Islamic teachings support women’s participation in economic activities; including handwork business can make a significant contribution to economic development of Doma. And recommends that policy makers and stakeholders take steps to promote and support women’s involvement in this sector. The study also identifies the challenges faced by women in handwork business and provides recommendations for promoting their participation.